Analysis and Prediction of Roughness of Face Milled Surfaces using CAD Model - Kundrak, Janos; Felho, Csaba; Nagy, Antal (Manufacturing Technology Journal, 2022)
The condition for the designability and efficiency of the machining processes is that the part production process is chosen to meet the operational requirements based on the most accurate technological plans possible. One part of this is the planning of the required quality and roughness of the surfaces and achievement of the required values in the finishing. In this paper, a study on the predictability of surface roughness was performed using a CAD model based on theoretical roughness and validated by cutting experiments. The reported results show the effect of the feed rate change in face milling for two tools with different edge geometries in planes parallel to the feed direction.
Keywords: Face Milling; Surface Roughness; Theoretical Roughness; CAD Modelling of Roughness; Roughness Estimation